RETRACTED: Ambient UV-B exposure reduces the binding of ofloxacin with bacterial DNA gyrase and induces DNA damage mediated apoptosis. (April 2016) - Singh, Jyoti; Dwivedi, Ashish; Mujtaba, Syed Faiz; Singh, Krishna P.; Pal, Manish Kumar; Chopra, Deepti; Goyal, Shruti; Srivastav, Ajeet K.; Dubey, Divya; Gupta, Shailendra K.; Haldar, Chandana; Ray, Ratan Singh
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Editor-in-Chief. The study is retracted due to image duplication reasons: The article contains an image that had already appeared in Free Radic Res, 48.3 (2014): 333–346. DOI 10.3109/10715762.2013.869324 . The images are used in both papers but to conclude something entirely different, and suggested that the images have an entirely different biological meaning and treatment. Duplicating images in this way is ethically not acceptable.